2009
DOI: 10.1177/0022466909344223
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of and Implications for Students Participating in Alternate Assessments Based on Alternate Academic Achievement Standards

Abstract: Little research has precisely defined the population of students participating in alternate assessments based on alternate academic achievement standards (AA-AAAS). Therefore, the purpose of this article is twofold: (a) explicate the findings of a multistate study examining the characteristics of the population of students participating in AA-AAAS, and (b) discuss the implications of those findings for instruction and assessment that move us closer to understanding what these students know and can do. The arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 14 publications
(23 reference statements)
3
67
1
2
Order By: Relevance
“…The gaps in skills widen as students progress through academic years, making it more and more difficult for students to access the general math curriculum and develop problem-solving skills. As the gap widens, the problem solving skills inherent in mathematics instruction beyond time and money, which are so important for success in post-school outcomes, become out of reach for students with severe intellectual disability (Kearns, Towles-Reeves, Kleinert, Kleinert, & Thomas, 2011). Two main factors contribute to the problem: (1) the sparseness of research on building the early numeracy skills, beyond number identification, for students with severe intellectual disability, and (2) an absence of instructional tools to build foundational numeracy skills to allow students access to mathematical problem solving (Browder, Jimenez, Spooner, Saunders, Hudson, & Bethune, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The gaps in skills widen as students progress through academic years, making it more and more difficult for students to access the general math curriculum and develop problem-solving skills. As the gap widens, the problem solving skills inherent in mathematics instruction beyond time and money, which are so important for success in post-school outcomes, become out of reach for students with severe intellectual disability (Kearns, Towles-Reeves, Kleinert, Kleinert, & Thomas, 2011). Two main factors contribute to the problem: (1) the sparseness of research on building the early numeracy skills, beyond number identification, for students with severe intellectual disability, and (2) an absence of instructional tools to build foundational numeracy skills to allow students access to mathematical problem solving (Browder, Jimenez, Spooner, Saunders, Hudson, & Bethune, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Towles-Reeves, Kearns, Kleinert, and Kleinert (2009; see also Kearns et al, 2011) found that a significant subset of SSCD taking AA-AAS had not yet acquired the use of fully symbolic modes of communication (i.e., the use of words, signs, or other means of formal language) but were still in the emerging symbolic (e.g., communication supported by picture and/or augmentative devices or gestural prompts) or presymbolic (e.g., communication primarily through facial expressions and changes in muscle tone) stages. In addition, SSCD had very inconsistent expressive and receptive communication, had low-level engagement, and required assistance with motor skills.…”
mentioning
confidence: 99%
“…For example, several studies have reported that students with the most significant cognitive disabilities participating in the AA-AAS experience notable difficulties in expressive and receptive communication and often require augmentative/ alternative communication systems (Almond & Bechard, 2005;Kearns et al, 2011;Towles-Reeves, Kearns, Kleinert, & Kleinert, 2009). However, these indicators also accurately describe some students with orthopedic impairments; expressive and receptive language disorders are commonly observed among individuals with cerebral palsy who do not have intellectual disabilities (Pellegrino, 2002).…”
Section: Discussionmentioning
confidence: 99%